2017
DOI: 10.1016/j.snb.2017.01.089
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of Tl(I) and In(III) using a voltammetric sensor array

Abstract: A sensor array consisting of a chemically modified sensor in which 4-carboxybenzo-18-crown-6 was immobilized onto a screen-printed carbon nanofiber-modified electrode (crown-6-SPCNFE) and an ex-situ antimony film deposited on a screen-printed carbon nanofiber-modified electrode (ex-situ-SbSPCNFE) was applied for the resolution of the strong overlapped signals resulting from the simultaneous determination of Tl(I) and In(III) by stripping voltammetry. A Partial Least Squares model was constructed and good calib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…References [238][239][240][241][242] Tables 1-2 and Tables 3-12 which are of increasing concern in pharmaceutic industry and environmental protection due to their intensive use as catalysers.…”
Section: Electrode Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…References [238][239][240][241][242] Tables 1-2 and Tables 3-12 which are of increasing concern in pharmaceutic industry and environmental protection due to their intensive use as catalysers.…”
Section: Electrode Arraysmentioning
confidence: 99%
“…In references[239,240] crown ethers are considered as modifiers and deposited via electrografting through diazonium salts. In[241] the electronic tongue comprises SPCNFEs modified with both antimony via ex-situ and a crown ether, whereas in[242] the four electrodes of the array are a SPCE, an ex-situ antimony SPCNFE and two peptide modified SPCNFEs. For data treatment artificial neural network (ANNs)[238][239][240] and partial least squares (PLS)[241,242] were considered.…”
mentioning
confidence: 99%
“…Electroanalytical sensors offer great opportunities to quantify the total indium amount at micromolar concentrations levels, using ex-situ plated antimony film [18][19][20] or bismuth film [21] electrodes. Another study reported the analytical performance of the adsorptive stripping electrochemical techniques (AdSV) in terms of linear ranges of calibration and limits of detection [22].…”
Section: Introductionmentioning
confidence: 99%
“…The working carbon layer can also be modified with novel carbon nanomaterials based on graphene, graphene oxide [ 112 ], carbon nanotubes, and carbon nanofibers [ 115 ], or carbon nanotubes/ionic liquid [ 116 ] that are added into the graphite carbon ink. Various sensor arrays, consisting of a combination of chemically modified SPEs and a commercial nanofiber-loaded SPE ex situ plated with Sb, have been applied for the simultaneous determination of metals that produce strongly overlapping stripping signals (Tl, In, Cd, Pb, Bi) in combination with chemometrical data treatment [ 115 , 117 ].…”
Section: Spes Modified With Sb and Snmentioning
confidence: 99%